Research Progress on Dynamic Uniform Load Characteristics of Planetary Gear Transmission - Li Kaiyang; Zhang Yijun; Wang Zhen; Zhang Guibin; Yan Shidang; Shi Lubing; Liu Zhongming (Jixie chuandong)
The distribution of the load on the tooth surface greatly affects the performance of the power split of the planetary transmission system. This study mainly studies the load sharing characteristics of the planetary gear transmission system and summarizes the current research status of this problem. The basic problems related to load sharing are expounded. Then, the analysis methods and calculation models of load sharing characteristics in planetary transmission are compared and analyzed. The methods and mechanisms of load-sharing which are commonly used at present are reviewed. It can be found that error is the root cause of uneven load distribution, and the most effective way to improve the uniform load is to reduce the sensitivity of the system to error. At present, dynamic analysis and the influence of nonlinear factors are the focus of research on uniform load problems. Floating parts and flexible parts are still commonly used uniform load methods.